Estudo patológico, padronização e uso da imuno-histoquímica em animais experimentalmente e naturalmente infectados com clostrídios histotóxicos - Prhiscylla Sadanã Pires (2011)
An immunohistochemistry (IHC) was optimized to detect C. septicum, C. chauvoei, C. novyi type A, C. perfringens type A and C. sordellii using tissues obtained from guinea pigs experimentally infected with these strains. Furthermore, we established the etiologic diagnosis of myonecrosis in a retrospective study of samples from Mato Grosso do Sul (MS). Primary antibodies were obtained after repeated inoculations (days 0, 28, 49, 70 and 91) of rabbits with reference strains of Clostridium histotóxicos. Purification of immunoglobulins was performed using an affinity chromatography column of protein G sepharose. For standardization of IHC technical, histological sections from inoculated animals were blocked and incubated successively with: primary antibody, which the dilution was previously standardized dilution, biotinylated secondary antibody and streptavidin peroxidase conjugate. The IHC was used to established the etiological diagnosis of myonecrosis in ruminant material from MS (n = 32). The protocol for the production of hyperimmune serum and the purification were considered satisfactory for obtaining primary antibody with high titers in the agglutination (1:1000 to1:100,000) and IHC (1:30 to 1:4,000). Most cases from MS showed positive signal for C. chauvoei (22%), followed by a positive C. perfringens type A (19%). Other samples showed an association of two or more agents. Concerning the frequency of each of the clostridia studied, C. chauvoei was the most prevalent (73.3%) among the sections classified as positive, followed by C. perfringens type A (53.3%), C. septicum (33.3%), C. sordellii (13.3) and C. novyi type A (10%). The standard technique was efficient to detect all clostridia tested. The distribution pattern of the rods and histological changes were similar in both groups of animals experimentally and naturally infected and confirm data previously reported. C. perfringens tipo A apparently is also a cause of mionecrosis in bovine and sheep. This evidence showed the importance of this agent and could be included in vaccines against black leg and gas gangrene.